2002
DOI: 10.2486/indhealth.40.371
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Caspase 3 Mediated Apoptosis in Hematopoietic Cytotoxicity of Metabolites of Ethylene Glycol Monomethyl Ether.

Abstract: The hematopoietic toxicity of ethylene glycol monomethyl ether (EGME) and its metabolites, methoxy acetaldehyde (MALD) and methoxyacetic acid (MAA), was analyzed using human bone marrow cells from a lymphoma patient without bone marrow involvement and a human leukemia cell line, HL 60. After 24-hour incubation, the concentrations of 50 percent inhibition (IC 50 ) of human hematopoietic progenitor cells with MALD or MAA were 3 mM and 3.9 mM, respectively, and EGME (10 mM or more) did not show any cytotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…A significant downregulation of caspase‐3 (Figure a–e) in T11TS treated glioma associated BMHSCs compared to glioma control BMHSCs clearly indicates its defensive anti‐apoptotic role against ENU mediated glioma orchestrated apoptosis of bone marrow HSCs in both the mature and immature compartments. This is in agreement with previous reports showing strong activation of caspase‐3, the main downstream caspase in methoxy acetaldehyde (MALD) induced apoptosis of human bone marrow cells and repression of apoptosis following treatments with cell permeable caspase‐3 inhibitors (Takagi et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…A significant downregulation of caspase‐3 (Figure a–e) in T11TS treated glioma associated BMHSCs compared to glioma control BMHSCs clearly indicates its defensive anti‐apoptotic role against ENU mediated glioma orchestrated apoptosis of bone marrow HSCs in both the mature and immature compartments. This is in agreement with previous reports showing strong activation of caspase‐3, the main downstream caspase in methoxy acetaldehyde (MALD) induced apoptosis of human bone marrow cells and repression of apoptosis following treatments with cell permeable caspase‐3 inhibitors (Takagi et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings showed organ-specific effects on developing germ cells. At the concentrations tested, all four compounds have been shown to be non-cytolethal in other cell lines [64][65][66][67][68][69][70]. Similarly, none of the compounds were cytolethal to somatic cells, and we did not observe overt cytolethality other than a 30% loss of viability with BPA.…”
Section: The Durand Model Can Be Used To Provide Mechanistic Insight ...mentioning
confidence: 48%
“…Alenzi et al (2002) reported that Fas and caspase activation may play an important role in regulating myeloid progenitor cell kinetics. Caspase-3 was also reported to play an important role in inducing hematopoietic toxicity by ethylene glycol monomethyl ether and its metabolites (Takagi et al, 2002). Furthermore, Page et al (2003) reported that 7,12-Dimethylbenz(a)anthracene caused pre-B cell apoptosis and immunotoxicity via activation of caspase-8 and -9.…”
Section: Discussionmentioning
confidence: 98%